Pelatihan Teknik Penyelamatan Diri di Perairan dalam Menunjang Keselamatan Pelayaran bagi Masyarakat di Desa Mariana, Banyuasin Palembang - Slamet Prasetyo; Yeti Komalasari; Fitri Masito (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2022)
Considering the enormous risk of work for people who work on ships, skilled, competent, and capable workers are needed to deal with emergency conditions that can cause loss of both property and life. The purpose of this community service activity is to provide education for the community around Mariana Village, Banyuasin Palembang regarding self-rescue techniques in the waters in order to minimize the impact of losses in the form of loss of property and life caused by accidents on board. The method used is training in the form of providing basic competence in self-defense techniques in waters using 4 hours of theory lessons in class and 4 hours of practical lessons in the field (1 lesson = 45 minutes). Overall this training activity went well and smoothly, with an average value of participant satisfaction responding strongly agreeing to 83.14%, a scale of 4 with a very good category (A) as an indicator that the participants' very positive response to the "Technical Training" activity Self-Rescue in Waters for the Community of Mariana Village, Banyuasin Palembang”. Through this activity, it was measured that of the 22 people who participated in the training, all of them did not have the competence of good water self-rescue techniques as regulated in the Safety of Life at Sea (SOLAS).